ORGANIZATION OF THE WORK IN A RECYCLING COOPERATIVE: IMPLICATIONS FOR THE HEALTH OF FEMALE WASTE PICKERS - Alexa Pupiara Flores Coelho; Carmem Lúcia Colomé Beck; Marcelo Nunes da Silva Fernandes; Rosângela Marion da Silva; Daiane Aparecida Martins do Reis (Universidade Federal do Paraná, 2016)
This study aimed to analyze the organization of the work of female waste pickers in a cooperative in the central region of the state of Rio Grande do Sul, Brazil. It is a qualitative, exploratory-descriptive study undertaken between July - August 2013, with data arising from participant observation and focus group sessions. The data were analyzed using thematic content analysis. The results evidence that, in spite of the workers having affinity for specified tasks, it is the difficulties that determine the organization of tasks in the cooperative. The organization of the work is influenced by the division of the work, and the lack of human resources (entailing overload) and appropriate equipment. The study points to the need for occupational support and a care network for female waste pickers, in the light of the occupational difficulties.